THE ROLE OF MUHAMMADIYAH IN BUILDING THE CIVILIZATION OF THE COMMUNITY OF THE BUTON ISLANDS - Suhendi Syam Syam; Dina Komalasari (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2021)
The purpose of this research is to reveal the role of Muhammadiyah in building the civilization of Butonese society. The research location is the Buton archipelago which consists of 6 districts and cities including Baubau city, Buton district, North Buton district, Central Buton district, South Buton district and Wakatobi district. This study used qualitative research methods. The results of this study can be concluded that the role of Muhammadiyah in building the civilization of Buton society includes the formation of organizations under the auspices of Muhammadiyah including PDM, PDA, Pemuda Muhammadiyah, IMM, IRM, AUM and Muhammadiyah branches. Apart from that in Buton there are also several Muhammadiyah schools ranging from RA, MI, SMA, and PTM, namely RA Aisyiyah in Baubau city, MIS Jabalnur, SMP Muhammadiyah Baubau, SMP Muhammadiyah 1 Tomia, SMA 1 Muhammadiyah Baubau, SMA 2 Muhammadiyah Baubau, SMA Muhammadiyah 1 Wakatobi. at Mola Wangi-Wangi Selatan, SMA 2 Muhammadiyah, and Muhammadiyah Buton University as well as several Muhammadiyah mosques. These charitable efforts are very helpful in building civilization, especially the Buton island community. With the various charities of Muhammadiyah's efforts, the people of Buton Islands are increasingly helped and their human civilization improves. The existence of Muhammadiyah on the island of Buton is certainly not free from the role of Muhammadiyah leaders who have sacrificed their wealth, energy, and thoughts on the island of Buton so that the civilization of the Buton island community from year to year is getting better and increasing. The number of Muhammadiyah figures recorded on the island of Buton is around 73 people. This research is the output of the Muhammadiyah Research Grant managed by the PP Muhammadiyah Diktilitbang Council in the 2019 funding year.Keywords: Role of Muhammadiyah, Civilization, and Buton Society